Developing a Sustainability Balanced Scorecard: A Case Study - Šukutytė, Inesa; Sakalauskaitė, Rugilė; Zaicaitė, Vanesa (Buhalterinės apskaitos teorija ir praktika, 2025)
This article explores the issue of sustainability management, focusing on the application of the Balanced Scorecard (BSC) for evaluating company sustainability. The aim of the study is to reveal the development process of such a system in an agricultural production company by analyzing the key aspects of creating a Sustainability Balanced Scorecard (SBSC). The relevance of the research stems from the growing need for companies in the agricultural sector to integrate sustainability principles into their performance assessment and to develop management systems that reflect not only economic but also social and environmental performance. The study is based on a descriptive case study strategy, drawing on the practical example of a single company and aiming to describe how the SBSC is implemented in practice. The findings indicate that the introduction of the SBSC enables better alignment of strategic goals with sustainability principles and fosters more socially responsible behavior. The results of the article may be useful for other companies in the agricultural production sector seeking to implement sustainability strategies and assess their effectiveness through an integrated and well-structured indicator system.